(untitled) (Journal of Forensic Medicine & Toxicology, 2013)
Identification of a person means determination of individuality. This is significant in almost all spheres of life. Identification is important in civil matters life, marriage, divorce, inheritance, paternity disputes, business contracts etc. Criminal cases like assault, murder, sexual offence etc. usually turn baseless in the absence of proper identification. There are various parameters of identification viz, name, age, sex, religion, race, fingerprints, footprints, DNA typing, congenital and acquired malformation etc. Out of these, stature is one of the important parameter. The stature prediction occupies relatively a central position both in anthropological research and in Forensic practice especially in cases where bodies are found in mutilated condition or only skeletal remain are sent for examination. In present study, stature is calculated from hand and foot length as well as breadth respectively and linear regression equation and multiplication factor has been developed for the population in central India.